2012
DOI: 10.1029/2011gm001073
|View full text |Cite
|
Sign up to set email alerts
|

Supermagnetic Storms: Hazard to Society

Abstract: Magnetic storms are an important component of space weather effects on Earth. Superintense magnetic storms (defined here as those with Dst < À500 nT, where Dst stands for the disturbance storm time index that measures the strength of the magnetic storm), although relatively rare, can be hazardous to technological systems in space as well as on the ground. Such storms can cause life-threatening power outages, satellite damage, communication failures, and navigational problems. The data for such magnetic storms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 57 publications
(64 reference statements)
1
30
0
Order By: Relevance
“…If we take an average solar wind density of ~5 cm −3 and a maximum compression ratio of ~4 as experimentally (Kennel, Edmiston, et al, ; Kennel, Scarf, et al, ; Tsurutani et al, ) and theoretically (Kennel, Edmiston, & Hada, ) shown for interplanetary space, we get a downstream sheath density of ~20 cm −3 . That taken with the Tsurutani et al () and Lakhina et al () derived solar wind speed of ~1,850 km s −1 at 1 AU gives a ram pressure of 114 nPa. This ram pressure can produce a Sudden Impulse (SI + ) of ~160 nT less ground induction effects (Araki et al, ; Siscoe et al, ; Tsurutani & Lakhina, ).…”
Section: Plasma Densitiesmentioning
confidence: 85%
“…If we take an average solar wind density of ~5 cm −3 and a maximum compression ratio of ~4 as experimentally (Kennel, Edmiston, et al, ; Kennel, Scarf, et al, ; Tsurutani et al, ) and theoretically (Kennel, Edmiston, & Hada, ) shown for interplanetary space, we get a downstream sheath density of ~20 cm −3 . That taken with the Tsurutani et al () and Lakhina et al () derived solar wind speed of ~1,850 km s −1 at 1 AU gives a ram pressure of 114 nPa. This ram pressure can produce a Sudden Impulse (SI + ) of ~160 nT less ground induction effects (Araki et al, ; Siscoe et al, ; Tsurutani & Lakhina, ).…”
Section: Plasma Densitiesmentioning
confidence: 85%
“…If such an interplanetary CME (ICME) with intense southward interplanetary magnetic fields collide with the Earth's magnetosphere, it will cause an SMS (Tsurutani et al 1992;Echer and Gonzalez 2008a). It is believed that the Carrington magnetic storm, the most intense magnetic storm (Dst = −1760 nT) in recorded history, was caused by an ICME that collided with the Earth on September 1-2, 1859 Lakhina et al 2012). The Carrington storm caused auroras to be visible down to ±23° magnetic latitude, at Hawaii and Santiago, Chile (Kimball 1960).…”
Section: Solar and Interplanetary Drivers Of Geomagnetic Stormsmentioning
confidence: 97%
“…The auroral reports based on newspapers and personal correspondences with Sydney Chapman (Kimball 1960; Loomis 1861), and recently obtained (space age) knowledge of interplanetary causes of intense storms were applied to determine the probable causes of this super magnetic storm event. Here, we will briefly review the main characteristics of this storm Lakhina et al 2005Lakhina et al , 2012. Figure 1 shows the deduced horizontal component magnetogram of September 1-2, 1859 from the Colaba Observatory recordings.…”
Section: Case History: Super Magnetic Storm Of September 1-2 1859mentioning
confidence: 99%
See 1 more Smart Citation
“…The large sunspot group (Group 520 in Carrington, Group 143 in Schwabe, and Group 219 in Secchi) caused a series of ICMEs, and a subsequent series of magnetic storms and auroral displays between 28 August and 4 September 1859 (Green & Boardsen, ; Hayakawa, Ebihara, Hand, et al, ; Kimball, ; Lakhina et al, ; Lakhina & Tsurutani, ).…”
Section: Auroral Evolutions and Magnetic Disturbancesmentioning
confidence: 99%